2020
DOI: 10.1177/0021998320966388
|View full text |Cite
|
Sign up to set email alerts
|

A novel particle-filled carbon-fibre reinforced polymer model composite tailored for the application of digital volume correlation and computed tomography

Abstract: This paper presents the development of novel Carbon-Fibre Reinforced Polymer (CFRP) laminates, tailored for the application of Digital Volume Correlation (DVC) and Computed Tomography (CT) to experimental mechanics analyses of these materials. Analogous to surface-based Digital Image Correlation (DIC), DVC is a relatively novel volumetric method that utilizes CT data to quantify internal three-dimensional (3D) displacements and implicit strain fields. The highly anisotropic and somewhat regular/self-similar mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Previous studies have shown that for low particle concentrations, the mechanical properties of thermosetting matrices can be largely preserved [47], [48]. In turn, by comparing the micromechanical behaviour of the particle-adapted material alongside its particle-free counterpart, we demonstrate elsewhere [49] that the response of the newly developed CFRP is consistent with standard production materials suggesting its suitability as a model system for mechanistic investigations.…”
Section: Introductionsupporting
confidence: 53%
“…Previous studies have shown that for low particle concentrations, the mechanical properties of thermosetting matrices can be largely preserved [47], [48]. In turn, by comparing the micromechanical behaviour of the particle-adapted material alongside its particle-free counterpart, we demonstrate elsewhere [49] that the response of the newly developed CFRP is consistent with standard production materials suggesting its suitability as a model system for mechanistic investigations.…”
Section: Introductionsupporting
confidence: 53%
“…• Schöberl et al [49] found similar fibre break development for two nominally identical specimens, but one did not reach final failure. There were only 4 and 6 volumes available at different load steps.…”
Section: Discussionmentioning
confidence: 96%
“…Raman spectroscopy is necessarily restricted to imaging fibres at specimen surfaces, and, in most cases, to single fibre specimens or specimens with low volume fractions. In recent years, the focus of experimental validations has, therefore, shifted towards the use of synchrotron radiation computed tomography (SRCT) [16,[42][43][44][45][46][47][48][49][50]. SRCT allows three-dimensional in-situ observation of fibres within the bulk of composites, albeit with small imaging volumes (~1 mm 3 ) at the required resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a general trend, the particle size, or actually the aggregate or agglomerate cluster size, is stated to decrease with increasing energy density and shows an inverse power law behaviour (~𝐶. 𝐸 " 12 ) [31,36]. Nevertheless, large powers or times have resulted in possible re-agglomeration; hence, the optimisation and general trends of a developed ultrasonication procedure remain a system-specific challenge [18][19]22,38].…”
Section: Introductionmentioning
confidence: 99%